Effects of self-regulated learning strategies on preschool children’s self-efficacy and performance in early writing / Siew Siew Kim - Siew, Siew Kim (2019)
Research suggests that early writing is crucial in the development of young children’s literacy skills and links to their conventional literacy outcomes in elementary school and beyond. In order to enhance the will and the skills to express thoughts explicitly and effectively in early writing among preschool children, selfregulated learning was suggested for preschool children as one of the effective learning approaches in this study. Grounded in Bandura’s social cognitive theory and Zimmerman Self-Regulated Learning Model, this quasi-experimental study involved seventy-five preschool children, aged from five to six years old who enrolled in two public preschools in Selangor, Malaysia. This study aimed to investigate the effectiveness of self-regulated learning strategies on early writing self-efficacy and early writing performance among preschool children. Quantitative data collection was engaged and supported with qualitative data through interviews to obtain a deep insight of the findings. Descriptive and inferential statistics were used to analysis the quantitative data. Interviews with eight children were conducted in order to obtain indepth information. Two-way Repeated Measure ANCOVA was employed and confirmed the effectiveness of self-regulated learning intervention with interaction effect between test and group for early writing self-efficacy was statistically significant (F(1, 72) = 12.665; p = 0.001, h2= 0.150), with Cohen’s d = 0.84; for early writing performance was statistically significant (F(1, 72) = 110.801; p < 0.001, h2= 0.606), with Cohen’s d = 2.84. Furthermore, self-monitoring & controlling (F(5, 69)=17.934, p < 0.001), with an adjusted R²=0.534 was confirmed as strong factor for early writing self-efficacy, whereas planning & goal setting (F(5, 69)=12.706, p< 0.001), with an adjusted R²= 0.442 was confirmed as strong factor for early writing performance. Interview data also revealed and supported that self-regulated learning strategies contribute to the complex writing tasks among out-performing children from the study. There were eleven strategies were mentioned during the interviews and employed pertaining to different contexts. According to the children, planning and goal setting, selfmonitoring and self-evaluation were the strategies that will assure their writing quality. Strategies such as seeking social help from peers or adults and seeking information from resources were frequently mentioned pertaining to classroom and at home context. The findings of this research provide a useful insight into early writing and self-regulated learning instructions in Malaysia preschool context. Implications such as content and pedagogy knowledge on early writing and self-regulated learning, classroom practices in preschools were highlighted in this study and recommendations for further study were made.